Effectiveness of municipal solid waste incinerators in replacing other fuels. A primary energy balance approach for the EU28. Issue 10 (October 2018) - Di Maria, Francesco; Sisani, Federico
The latest European Union legislation introduced the possibility of considering high efficiency incineration of waste as a recovery operation, that is, to use waste as a means of producing energy and hence able to replace other fuels. This possibility has been further investigated by expanding the boundaries for the mass and energy balance of municipal solid waste incinerators operating in the EU28. An energetic analysis based on a hybrid primary energy (MJ Mg -1 ) approach was performed also using the cumulative energy demand index. Average results showed a net hybrid primary energy >0 for those municipal solid waste incinerators recovering only electricity, indicating that no primary energies can be replaced. For those operating in combined heat and power mode, an average hybrid primary energy ranging from about −200 MJ Mg -1 to about −4800 MJ Mg -1 was detected for large-size municipal solid waste incineration facilities (>200, 000 Mg y -1 ). The value of hybrid primary energy for medium and small facilities ranged from about +3000 MJ Mg -1 to −4000 MJ Mg -1 . Furthermore, in some operating conditions landfill had a lower hybrid primary energy than those of small-size municipal solid waste incinerators. To some degree, these results are not in agreement with the classification of municipal solid waste incinerators based on the energy efficiency formula, particularly for those recovering only electrical energy.